Implementation of Mechanization into the Welding Process - Taraba, Milos; Vavro, Jan; Vavro, Jan (Manufacturing Technology Journal, 2025)
The article is focused on the investigation of the impact of the implementation of mechanization into the welding workplace, for the production of cylinders from austenitic X5CrNi18 10 chromium nickel steel. The welds are assembled into a production line for the processing of puff pastry. In addition to the technical improvement of the process and the verification of the sufficient quality of the welds, calculations were used to prove that after the implementation of the change, there was a significant reduction in the production time. By introducing a higher level of mechanization and necessary technological changes, the production time was reduced by up to half, compared with the original technological procedure, including an increase in quality parameters and it led to a reduction in the production costs of the welding workplace. A significant consequence of the proposed change was connected with its impact on workplace safety.
Keywords: Austenitic chromium-nickel steel; Implementation; Mechanization; Welding process; Positioner